POTENSI POLA ALIRAN MUDIK PADA MASA PANDEMI COVID-19 - Ari Purwanto Sarwo Prasojo; Yulinda Nurul Aini; Dwiyanti Kusumaningrum (Jurnal Kependudukan Indonesia, 2020)
Millions of people in Indonesia traditionally return to their home town every year in a tradition called "mudik". Unlike previous years, the annual tradition has become a cause for concern after COVID-19. This article presents the potential of mudik flows patterns during the COVID-19 pandemic, which were divided into 11 regions. We use a circlize plot chord diagram to show the potential of mudik flows patterns based on primary survey data on community perceptions regarding mobility and transportation during COVID-19. The results show that the most massive mudik flow is expected to occur from Jabodetabek to Central Java. Jabodetabek is the highest mudik origin, while Central Java and East Java are the highest mudik destinations. We suggest that government should anticipate the spread of COVID-19 by limiting mobility as they have been done this year. In addition, this must also be supported by citizen's awareness and coordination between local governments.